2005
DOI: 10.1128/jb.187.8.2783-2792.2005
|View full text |Cite
|
Sign up to set email alerts
|

Cross-Resistance of Escherichia coli RNA Polymerases Conferring Rifampin Resistance to Different Antibiotics

Abstract: In this study we further defined the rifampin-binding sites in Escherichia coli RNA polymerase (RNAP) and determined the relationship between rifampin-binding sites and the binding sites of other antibiotics, including two rifamycin derivatives, rifabutin and rifapentine, and streptolydigin and sorangicin A, which are unrelated to rifampin, using a purified in vitro system. We found that there is almost a complete correlation between resistance to rifampin (Rif r ) and reduced rifampin binding to 12 RNAPs puri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
47
0

Year Published

2007
2007
2017
2017

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 62 publications
(47 citation statements)
references
References 41 publications
(42 reference statements)
0
47
0
Order By: Relevance
“…Here M 3 and M 5 represent oligomers just a handful of nucleotides long that are the abortive mRNA-like transcripts produced when rifampicin-like drugs are bound to RNA polymerase [26]. However, this more complicated model does not provide any additional theoretical insight into the interaction of drugs targeting the same enzyme; (C 1) is already sufficient to have non-trivial, synergistic drug interactions as we now aim to show.…”
Section: Appendix C Synergy Results From Two Antibiotics Targeting Omentioning
confidence: 99%
“…Here M 3 and M 5 represent oligomers just a handful of nucleotides long that are the abortive mRNA-like transcripts produced when rifampicin-like drugs are bound to RNA polymerase [26]. However, this more complicated model does not provide any additional theoretical insight into the interaction of drugs targeting the same enzyme; (C 1) is already sufficient to have non-trivial, synergistic drug interactions as we now aim to show.…”
Section: Appendix C Synergy Results From Two Antibiotics Targeting Omentioning
confidence: 99%
“…As precedence, Xu et al showed that E. coli H526Y RNAP had complete resistance to the RNAP inhibitor sorangicin A while mutants D516N and S531F, and other residues, showed only partial or no resistance. 29 Two of the four compounds in cluster 6 (186618 and 193157) showed activity against M. tuberculosis in culture (Table 1). Interestingly, compound 193157 was active in culture despite being inactive against WT MTB RNAP in vitro.…”
Section: Discussionmentioning
confidence: 99%
“…Although RIF binds in the RNA tract, many of the residues in the RIF binding pocket do not directly contact the RNA. Numerous mutations in the RNA polymerase β-chain confer RIF resistance (RIF R ) in Escherichia coli and Mycobacterium tuberculosis [Xu et al, 2005;Makiela-Dzbenska et al, 2011;Zhou et al, 2013;Jin and Gross, 1989;Sandgren et al, 2009;Barrick et al, 2010]. These mutations are clustered in 4 regions of RNA polymerase β, termed RIF R -determining regions (RRDRs) N, I, II, and III [Molodtsov et al., 2016].…”
mentioning
confidence: 99%